(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objectives of this research were to estimate volume ofcharcoal produced per unit area of Acacia seyal plantations atWadelbashier Forest Reserve and to estimate financial profitability(US ha-1 ) of charcoal production, using net present value (NPV) as adecision criterion. Data on tree growth was collected, using fixed-radiustemporary circular sample plots. Present and harvest age standing woodvolumes were estimated. Market-related data were collected throughstructured interviews of key informants of the staff of Forest NationalCorporation (FNC) of Algadarif State, members of Trade Union ofFuelwood Producers and Traders, and from secondary sources of thestate forestry service. The results indicated that the present standingwood volume (m3 ha-1 ) ranged between 8.4 and 26.2 and that charcoalproduction from A. seyal plantations managed for a rotation of 20 yearsat 12% annual discount rate yielded a negative mean financial NPV ofUS ha-1 -30.3 indicating that charcoal production at current stocking,factor costs, output prices, a 12% annual discount rate and a rotationlength of 20 years is not financially profitable. The study concludes thatpolicy and management interventions are inevitable for sustainableproduction.